“Our Teaching Is Rocking Their Ontological Security”: Exploring the Emotional Labour of Transformative Criminal Justice Pedagogy - Marian Duggan; Charlotte Bishop (Social Sciences, 2023)
Feminist scholars teaching criminology, criminal justice, and law actively address issues of gendered and intersectional importance as crucial additions to degree programmes. Their inclusive acts illustrate a critical pedagogic approach to representing a diverse range of identities and experiences which is necessary to affect the kind of transformational learning that may resonate and impact upon graduate justice practitioners. However, the personal and professional impacts involved in seeking to effect positive developments in social and criminal justice often go unnoticed. This article presents empirical research findings exploring criminal justice tutors’ experiences of undertaking transformative teaching using feminist pedagogies. It provides insight into the lived experiences shared by scholars which highlights the affective nature of this work and offers recommendations for others navigating the neoliberal academy.